The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/ijgm.s379592
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 Symptoms Distribution According to Tobacco Products Consumption and Khat Chewing: A Potential Antinociceptive Role of Nicotine Among COVID-19 Patients

Abstract: Purpose To assess the distribution of COVID-19 symptoms according to the consumption of tobacco products and khat chewing among samples of Saudi Arabian individuals. Methods This retrospective cohort study was conducted in the Jazan region of Saudi Arabia. Data was collected online via a self-administered questionnaire. The questionnaire measured demographic variables, COVID-19 symptoms and vaccination, comorbidities history, tobacco product consumption, and khat chewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In a study by Gosadi et al, which recruited a sample of 1,026 individuals in Jazan, Saudi Arabia, to assess clinical presentation related to COVID-19 infection, it was reported that the most frequently reported clinical presentations were related to fever and headache [27]. They also reported that patients diagnosed with asthma were more likely to suffer from respiratory symptoms related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Gosadi et al, which recruited a sample of 1,026 individuals in Jazan, Saudi Arabia, to assess clinical presentation related to COVID-19 infection, it was reported that the most frequently reported clinical presentations were related to fever and headache [27]. They also reported that patients diagnosed with asthma were more likely to suffer from respiratory symptoms related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%